Correlation of urinary biomarkers (Interleukin-6, Transforming growth factor-β, E-Cadherin, and MCP-1) with conventional parameters of disease progression in patients of posterior urethral valves: A comparative analysis - Priyanka Garg Mittal; Ram Samujh; Nitin James Peters; Sadhna Sharma (Wolters Kluwer Medknow Publications, 2022)
Aims: Posterior urethral valves (PUV) are the leading cause of end-stage renal disease in boys. The study aimed to look at the ongoing renal damage and profibrotic activity by measuring the levels of Interleukin-6 (IL-6), Transforming growth factor-β (TGF-β), E-cadherin, and Monocyte Chemoattractant Protein-1 (MCP-1) and observing trends in subsequent follow-ups and at the same time correlating them with the established parameters of disease progression. Materials and Methods: This prospective study included 36 consecutive patients of PUV, managed over a period of 18 months. IL-6, TGF-β, E-cadherin, and MCP-1 were measured in urine samples at the time of admission, pre-fulguration and 3 months' and 9 months' post fulguration. The observed values were correlated with the conventional parameters used in clinical practice. Results: All the biomarkers showed statistically significant trends when these values were compared on admission, postoptimization and 3 months' and 9 months' postfulguration. None of the biomarkers showed a significant correlation with renal function tests. E-Cadherin and TGF-β showed a positive and a negative correlation with ultrasonography (USG) kidney, ureter, and bladder (KUB) respectively. E-Cadherin showed a positive correlation, whereas IL-6 and TGFβ showed negative correlation respectively with micturating cystourethrogram (MCUG). IL-6 showed statistically a significant negative correlation with dimercapto succinic acid (DMSA). MCP-1 did not show any significant correlation with USG KUB, MCUG and DMSA. Conclusion: This study concludes that E-Cadherin, IL-6, TGF-β can be promising urinary biomarkers for early detection of the ongoing renal damage in patients of PUV following valve fulguration. MCP-1 may have more complex interactions, with inflammatory markers; which warrants further research.